Behavior and exocrine glands in the myrmecophilous beetle Lomechusoides strumosus (Fabricius, 1775) (formerly called Lomechusa strumosa) (Coleoptera: Staphylinidae: Aleocharinae). - Bert Hölldobler; Christina L Kwapich; Kevin L Haight (PLoS ONE, 2018)
To become integrated into an ant society, myrmecophilous parasites must overcome both the defenses and the communication system of their hosts. Some aleocharine staphylinid beetles employ chemical and tactile strategies to invade colonies, where they later consume ant brood and participate in parasitic trophallaxis with host ants. By producing compounds that both appease their hosts and stimulate adoption, the beetles are able to live in and deposit their own eggs in the well defended ant nest. In the current paper, previous findings on the myrmecophilous behavior and morphological features of the staphylinid beetle Lomechusoides (formerly Lomechusa) strumosus are reviewed and re-evaluated. Hitherto unpublished results concerning the beetles' ability to participate in the social food flow of their host ants are reported. Furthermore, we present an analysis and documentation of the behavioral interactions between beetles and host ants during the adoption process, and we report new histological and scanning electron microscopic analyses of the exocrine glands and morphological adaptations that underlie the myrmecophilous behavior of L. strumosus. The main features of L. strumosus are compared with those of the staphilinid myrmecophile Lomechusa (formerly Atemeles) pubicollis. The paper concludes with a description of the life trajectory of L. strumosus and presents a brief history and discussion of the hypotheses concerning the evolution of myrmecophily in L. strumosus and other highly adapted myrmecophilous parasites.